Immunolocalization of IL-6 and IL-10 in the testicular tissue of testicular dysfunction rat treated with secretome - Prihatno, Surya Agus; Adi, Yosua Kristian; Budipitojo, Teguh (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: This study was carried out to find out the immunolocalization of Interleukin 6 (IL-6) and Interleukin 10 (IL-10) in the testicular tissue of testicular dysfunction rat treated with secretome from human umbilical stem cells. Materials and methods: Rats were induced with cisplatin for testicular dysfunction condition. After that, the rats were grouped into two categories and were treated with secretome at 0.2 and 0.5 ml/kg BW once every week for 4 weeks. One week later, after the secretome treatment, the rats were sacrificed for histological evaluation using the immunohistochemical method. The preparation slides were examined using a light microscope and were analyzed descriptively and quantitatively. Results: There were no IL-6 and IL-10 immunoreactivities seen in the testicular tissue after cisplatin induction. However, the immunoreactivities of IL-6 and IL-10 were detected after secretome treatment, with both dosages of 0.2 and 0.5 ml/kg BW. These immunoreactivities were detected in the spermatogonia, spermatid/luminal tissue of seminiferous tubule, spermatogenic cells, and Leydig cells. In the cell calculation, the numbers of IL-6 immunoreactive cells were higher at the lower secretome dosage. In contrast, the numbers of IL-10 immunoreactive cells were higher at the higher secretome dosage. Conclusion: IL-6 and IL-10 can be localized in the testicular tissue of testicular dysfunction rat after secretome treatment. J. Adv. Vet. Anim. Res., 7(3): 514-520, Sep 2020 http://doi.org/10.5455/javar.2020.g448